The post-tensioned concrete technique in the work of Eduardo Torroja. The case of the Church of San Nicolás in Gandía. (February 2020) - Arnau-Paltor, F.; Serrano-Lanzarote, B.; Fenollosa, E.
Abstract: The renowned Spanish engineer Eduardo Torroja Miret, (1899–1961), was a pioneer in the use of prestressed concrete in Spain, using it in a varied and ingenious way in many of his works. This technology enabled him to achieve the desired structural behaviour while guaranteeing the water tightness of reservoirs and piping. His deep structural knowledge and professional experience allowed him to develop the prestressing and anchoring method patented as the Barredo Method, which internationally competed with the most recognised ones as BBRV or Freyssinet. One of the most interesting examples in the application of this technique is the Church of San Nicolás in Gandía (1962), which was the last of Torroja's works. With an asymmetrical cross-section 15 cm thick, two thin folded plates span 29 m. His structural analysis shows that post-tensioning minimizes biaxial bending effects and corrects torsion issues.